A new species of Ansonia Stoliczka 1872 (Anura: Bufonidae) from Central Peninsular Malaysia and a revised taxonomy for Ansonia from the Malay Peninsula. Zootaxa, 1327, 1–21. (ERRATUM) - Grismer, L. L. (Zootaxa, 2006)
ERRATUM